Prevalence of hypertension and its associated factors among adults living in Pokhara metropolitan city - Gurung, Bishnu; Thapa, Nirupa; Paudel, Usha Kiran (Journal of Gandaki Medical College-Nepal, 2022)
Introduction: Hypertension is one of the silent killer diseases affecting multiple organs. Hypertension prevalence is increasing in developing countries. So, the present study was conducted to find out the prevalence and associated factors of hypertension among adults living in Pokhara metropolitan city.Methods: This was a community-based cross-sectional study conducted in Pokhara metropolitan city. Study participants were aged 18 to 70 years, residing permanently in the study sites. Wards, households, and respondents were selected randomly. Data was entered in Epi Data and analysed using SPSS 16 version. Descriptive statistics and inferential statistics at 5% level of significance were used.Results: Of the 293 participants, 60.8% were females, mean (standard deviation) of age was 41.7(14.6) years, 29.3% had no formal education, 35.1% were brahmins, and 41.2% were homemakers. Prevalence of hypertension was 35.5%. Age, gender, education, marital status, smoking, alcohol consumption, salt adding habit, presence of diabetes status, use of cholesterol drugs and body mass index were significantly associated with hypertension. In multivariate analysis, age, gender, alcohol consumption, salt adding habit and body mass index were identified as significant factors for hypertension.Conclusions: The study concluded that the prevalence of hypertension in Pokhara metropolitan city was alarming. There were greater number of pre-hypertension cases which are in turn at great risk of developing hypertension if not intervene timely. Therefore, community awareness program on hypertension and its preventive measures is must in preventing the dreadful complications.